Kimbanguism 100 Years On
XVII, 167 p. 4 illus.
Keywords: From its genesis in 1921, Kimbanguism has constituted one of the most fascinating socio-cultural movements of the Kongo region. This interdisciplinary collection covers the socio-cultural dynamics of the Kimbanguist church and its contribution to African studies over the past hundred years. Scholars renowned for their Kongo studies work, such as Wyatt MacGaffey, John M. Janzen, and John K. Thornton, contributed to this collection. Adrien Nginamau Ngudiankama is the founder of Kongo Academy, Inc, (www.kongoacademy.org). He holds a Master of Philosophy in Systematic Theology from King's College as well as a PhD in Health Education and Health Promotion from the Institute of Education at the University of London.